A method for retrieving char oxidation kinetic data from reacting particle trajectories in a novel test facility. (15th January 2018) - Adamczyk, Wojciech P.; Białecki, Ryszard A.; Ditaranto, Mario; Haugen, Nils Erland L.; Katelbach-Woźniak, Anna; Klimanek, Adam; Sładek, Sławomir; Szlęk, Andrzej; Węcel, Gabriel
Graphical abstract: Highlights: A novel method for retrieving coal combustion kinetics was developed. Particle density and mean reaction were rate determined by an inverse method. Sensitivity study and uncertainty quantification of model output was performed. Results of coal char combustion in air was compared with TGA results. Coefficients of a kinetic-diffusion model for combustion in air were determined. Abstract: In this paper, a new method for retrieving char combustion rates is presented. The method is based on an observation that the curvature of a trajectory of a freely falling and reacting char particle in a horizontal laminar flow changes due to the change of the particles mass. An experimental facility was designed and built allowing for recording reacting particle trajectories and determining oxidation kinetics. A brief description of the experimental facility and measurement procedure is given. In this procedure, a model of a freely falling particle in a laminar horizontal flow was developed. The model comprises a set of ordinary differential equations that predict a particle trajectory for given rate constants. The trajectory predicted by the model is then fitted to the measured trajectories by changing the rate constants. The best fit corresponds to the mean rate constant. Moreover, measurement results for Janina coal char combustion in air at various temperatures are presented. The key input parameters of the model are identified by a global sensitivity analysis, and the uncertainty in the results is quantified. The method is validated by comparison with TGA results obtained from the literature. Finally, the experimental data are used to determine rate coefficients of a kinetic-diffusion surface combustion model. The presented methodology is suitable to determine the kinetic data, however its further development is required in order to improve the accuracy of the measurements and include the more complex physico-chemical processes that occur during carbon conversion.